Conceptual Design of Distillation Systems - F. Doherty M (Mc Graw Hill, 2001)
This book is written for engineers both in school and in the real world. The ideas are clear and well organized. Malone and Doherty have a knack for 'distilling' the important concepts out of a complex project and enabling the reader to learn how to do the same.